Bahasa Inggris - Riza Reka Atin; Sunarto (Jurnal Akuntansi Dan Manajemen, 2025)
The Capital Market is a place for companies to obtain capital from investors. Investors in Indonesian Capital Market come from individual investors and institutional investors. According to the Indonesian Central Securities Depository, the number of individual investors in January 2024 reached 12,126,768, with a percentage of 99.66%. Investors should know the information about Stock Price and the factors that affect company's Stock Price before investing funds in a company so that investor do not make mistakes in the decision-making process. The purpose of this research is to analyze the impact of Liquidity and Leverage on Stock Price with Profitability as the moderating variable. The researcher took up this topic because the Profitability variable indicates how much profit a company is making, so it is hoped that this variable can moderate the independent variable on Stock Price. The analytical methods used are tests of descriptive statistics tests, normality test, classical assumption tests, including tests of multicollinearity, heteroscedasticity, and autocorrelation tests, multiple regression test, model tests and hypothesis test. The sampling method used in this research is the purposive sampling method, so that the sample of 116 samples was obtained. The results of this research showed that Leverage (Debt to Equity Ratio) and Profitability (Return on Assets) are negatively significant to Stock Price, while Liquidity (Current Ratio) is negatively insignificant to Stock Price. The Profitability variable (Return on Assets) is not able to moderate the independent variable on Stock Price. Therefore, it can be concluded that Leverage and Profitability have a negative effect on Stock Price, while Liquidity has no effect on Stock Price. Profitability variable cannot moderate the independent variable of Stock Price. The implications that the researchers can provide are that investors are expected to consider the factors that affect the company's Stock Price before investing their funds in the company. Companies are also expected to take note of the findings and make them a benchmark for companies to perform well.